Paisaje social de Lima - Kapsoli Escudero, Wilfredo (2018)
The city of Lima, since its foundation (January 18, 1535) to the present, has un- dergone a gradual transformation both in its urban structure and in its population. This process, however, became faster and even violent as of the 80s of the last cen- tury with the emergence and action of the Tupac Amaru Revolutionary Movement and the Shining Path. The decade of the war of 1980 to 1990 made complete populations move from the countryside to the city, in such a way that Lima ended up being the biggest city of the country with people from the mountains. We want, on this occasion, to refer to the social composition of Lima that appears in Ricardo Palma’s Peruvian Traditions.